Vignettes of Violence: Exploring Trauma in Selected Poems of Wilfred Owen: Exploring the Grotesque Reality of War through Wilfred Owen's Poems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
War is an inevitable occurrence in human civilization. Poetry is mankind’s confidant since its dawn. Epics of all the cultures predominantly praise the war heroes, and regards participation in war and ensuring eventual victory as the sine qua non of manhood. However, cataclysmic consequence of war is a premonition to the entire civilization. War not only imperils physical loss but forges a permanent sore in the psyche of an individual andor community. World War I (1914-18) heralds a significant turn in the conception regarding war. The whole world gets terrified, experiencing the ‘needless butchery’ of human life. This concern paves the path of a considerable bulk of anti-war poetry. Wilfred Owen (1893-1918), perhaps the most celebrated poet of this group, exploits his first hand experience of the battle field as a testimony to depict the grotesque reality of war. To him war is analogous to despair and futility. His enterprise is directed not to a particular war but to any war which entices andor forces young and promising souls to the front with a false assurance of return and redemption. The present paper seeks to re-read some of the often anthologized poems of Owen, “Dulce et Decorum Est”, “Mental Case”, “Insensibility” and “Strange Meeting”, conceding his proclaimed attitude to war. The paper also offers symmetrical study between Owen the agonized soldier and Owen the anguished poet, insisting that the man who suffers and the mind which creates are hardly inseparable. Finally it argues that the poems’ appeal is conditioned by Owen’s experience of the trauma of war, both as a poet and a soldier.